Chronic effects of air pollution on lung function after lung transplantation in the Systems prediction of Chronic Lung Allograft Dysfunction (SysCLAD) study. Issue 1 (19th January 2017) - Benmerad, Meriem; Slama, Rémy; Botturi, Karine; Claustre, Johanna; Roux, Antoine; Sage, Edouard; Reynaud-Gaubert, Martine; Gomez, Carine; Kessler, Romain; Brugière, Olivier; Mornex, Jean-François; Mussot, Sacha; et al.
An irreversible loss in lung function limits the long-term success in lung transplantation. We evaluated the role of chronic exposure to ambient air pollution on lung function levels in lung transplant recipients (LTRs). The lung function of 520 LTRs from the Cohort in Lung Transplantation (COLT) study was measured every 6 months. The levels of air pollutants (nitrogen dioxide (NO2 ), particulate matter with an aerodynamic cut-off diameter of x µm (PMx ) and ozone (O3 )) at the patients' home address were averaged in the 12 months before each spirometry test. The effects of air pollutants on forced expiratory volume in 1 s (FEV1 ) and forced vital capacity (FVC) in % predicted were estimated using mixed linear regressions. We assessed the effect modification of macrolide antibiotics in this relationship. Increased 12-month levels of pollutants were associated with lower levels of FVC % pred (−2.56%, 95% CI −3.86–−1.25 for 5 µg·m −3 of PM10 ; −0.75%, 95% CI −1.38–−0.12 for 2 µg·m −3 of PM2.5 and −2.58%, 95% CI −4.63–−0.53 for 10 µg·m −3 of NO2 ). In patients not taking macrolides, the deleterious association between PM and FVC tended to be stronger and PM10 was associated with lower FEV1 . Our study suggests a deleterious effect of chronic exposure to air pollutants on lung function levels in LTRs, which might be modified with macrolides. Chronic exposure to air pollutants is associated with reduced lung function in lung transplant recipients http://ow.ly/gH8e304Qac4